Papillary Endolymphatic Sac Tumor: A Case Report. (17th July 2012) - Arava, S.; Soumya, R. M.; Chitragar, S.; Safaya, R.; Chandrashekhar, S. H.; Thakar, Alok
Abstract : Glandular tumors involving the middle ear are rare and distinguishing between adenoma and adenocarcinoma remains difficult. A distinct subclass of these tumors demonstrates microscopic papillary architecture and has a propensity to erode the petrous bone and extend intracranially. The term "aggressive papillary middle ear tumor" has recently been proposed to describe this more invasive type of middle ear tumor. These tumors cause symptoms even when microscopic in size. Although histologically benign, they have been locally destructive with frequent intracranial extension and patients may die of uncontrolled local disease. These tumors do not metastasize but there is single case report of drop metastasis to the spine in the literature. Hence this tumor must be distinguished from other benign tumors of the middle ear. These rare neoplasms constitute a distinct pathological entity and deserve wider recognition.